Penerapan Model Cooperative Learning Tipe NHT Menggunakan Media Pebelajaran Rolling Ball Game terhadap Hasil Belajar Pada Kelas XI Madrasah Arifah Gowa - Jafar, Andi Ferawati (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
This study aims to determine the learning outcomes of students using the NHT type cooperative learning model using rolling ball game learning media on learning outcomes in class XI Madrasah Arifah Gowa. The research method used is quasi-experimental with Noneequivalent control group design. The sample of this research is class XI.1 as many as 32 people and XI.2 as many as 27 people. Data collection is done by using a test of learning outcomes in the form of multiple choice questions. The statistical methodused descriptive analysis, inferential analysis, homogeneity test and hypothesis testing. Based on the results of calculations using the independent sample t-2 test using IBM SPSS v.20 obtained a value of 4.838 and the t table is sought by referring to the formula (α/2); (df) is equal to (0.05/2) ; (57). So that the value of the t table in the distribution of the t value of the statistical table is 2.002, thus the t-count value is 4.838 > t-table 2.002, so based on decision making through the comparison ofthe t-value with t-table, it can be concluded that H0 is rejected and H1 is accepted, which means there are differences in physics learning outcomes between the control and experimental classes or in other words the application of the lecture model with the NHT type cooperative learning model using the rolling ball game learning media will produce different physics learning outcomes. The implication of this research is that it is expected that educators can apply the NHT type cooperative learning model using rolling ball game learning media as an alternative in the teaching learning process to improve student learning outcomes.